A Mine Information System Based on an OMT Model of the Mine and the Deposits - Walter Keune (Society for Mining, Metallurgy & Exploration, 1996)
Object Modeling Technique. This formal descriptive language makes it possible to formulate requirements in the real world in such a way that they can be implemented in the form of entities (cf. Entity Relationship Model[Che83]) and methods (see Figure 1). The object Roadway is graphically depicted by means of the Polygon method.